Electrochemistry and spectroelectrochemistry of tert-butylcalix[4]arene bridged bis double-decker lutetium(111) phthalocyanine, Lu2Pc4 and dimeric lutetium(III) phthalocyanine, Lu2Pc2(OAc)(2) - ÖZKAYA, ALİ RIZA; KOCA, ATIF (ELSEVIER, 2007)
In this study, electrochemical, electrochromic and spectroelectrochemical properties of a tert-butylcalix[4]arene bridged bis doubledecker lutetium(III) phthalocyanine (Lu2Pc4 2) were investigated explicitly as compared with a tert-butylcalix[4]arene bridged dimeric lutetium(III) phthalocyanine [Lu2Pc2(OAc)(2) 1]. Distinctive differences between electrochemical and electrochromic properties of 1 and 2 were detected. Moreover, the properties of 1 and 2 were compared with previously reported S-4(CH2)(4) bridged Lu2Pc2(OAC)(2) and Lu2Pc4. The calixarene bridged phthalocyanine (Pc) compounds, 1 and 2 showed well-defined clectrochromic behaviour with green-blue and blue-purple colour transitions. The enhanced electrochromic properties of 2, as compared to 1, were attributed to its double-decker structure, probably allowing the formation of suitable ion channels for the counter ion movement in the solid film. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: electrochemistry; spectroelectrochemistry; electrochromism; phthalocyanine; double-decker; LANGMUIR-BLODGETT-FILMS; ELECTROCHROMIC PROPERTIES; SPECTROSCOPIC CHARACTERIZATION; ELECTRICAL-CONDUCTIVITY; COMPLEXES; DIPHTHALOCYANINE; ELECTRODES; BEHAVIOR